2015
DOI: 10.1186/s13012-016-0425-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a strategy that uses educational games to implement clinical practice guidelines among Spanish residents of family and community medicine (e-EDUCAGUIA project): a clinical trial by clusters

Abstract: BackgroundClinical practice guidelines (CPGs) have been developed with the aim of helping health professionals, patients, and caregivers make decisions about their health care, using the best available evidence. In many cases, incorporation of these recommendations into clinical practice also implies a need for changes in routine clinical practice. Using educational games as a strategy for implementing recommendations among health professionals has been demonstrated to be effective in some studies; however, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…academic publications and books), clinical reasoning can best be trained by repeated exposure to real patient cases [ 24 ]. It has been suggested that e-learning can be an effective tool for implementing clinical practice guidelines [ 25 ], and a multicentre clinical trial testing this hypothesis is currently underway [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…academic publications and books), clinical reasoning can best be trained by repeated exposure to real patient cases [ 24 ]. It has been suggested that e-learning can be an effective tool for implementing clinical practice guidelines [ 25 ], and a multicentre clinical trial testing this hypothesis is currently underway [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Portugal Del Cura-Gonzalez et al conducted a study to assess the effectiveness of a teaching strategy for the implementation of clinical guidelines using educational games [8]. They presented the findings for the use of an e-learning game EDUCAGUIA to improve knowledge and skills related to clinical decision-making by residents in family medicine.…”
Section: Related Workmentioning
confidence: 99%
“…Such evaluation is very important and it reflects the usefulness of utilizing games in teaching guidelines. We plan to conduct similar evaluation of our gamification approach with healthcare professionals in future [8].…”
Section: Related Workmentioning
confidence: 99%
“…En España, en la experiencia de Melús-Palazón, et al (41), se usó un ambiente social virtual para realizar conferencias, y se señala que las sociedades que agremian a los médicos familiares son importantes para mejorar la aceptación de los programas de educación a distancia entre ellos, así como para fomentar una relación de compañerismo, respeto y colaboración entre colegas y las capacidades para compartir conocimientos con sus pares (42). Paralelo a esto, en Colombia los médicos familiares se agremian en la Sociedad Colombiana de Medicina Familiar (SOCMEF), la cual tiene entre sus estatutos, participar junto con otras instituciones en los procesos formativos de los especialistas.…”
Section: Agremiación Médica Y Educación Continuada En Medicina Familiarunclassified